2021
DOI: 10.3389/fcimb.2021.665444
|View full text |Cite
|
Sign up to set email alerts
|

Development of miRNA-Based Approaches to Explore the Interruption of Mosquito-Borne Disease Transmission

Abstract: MicroRNA (miRNA or miR)-based approaches to interrupt the transmission of mosquito-borne diseases have been explored since 2005. A review of these studies and areas in which to proceed is needed. In this review, significant progress is reviewed at the level of individual miRNAs, and miRNA diversification and relevant confounders are described in detail. Current miRNA studies in mosquitoes include four steps, namely, identifying miRNAs, validating miRNA-pathogen interactions, exploring action mechanisms, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 97 publications
(461 reference statements)
0
8
0
Order By: Relevance
“…However, the anticancer effect and the mechanism of action of amentoflavone in CRC are unknown. In this study, we demonstrated the anti-CRC cell migration, invasion, and EMT effect of amentoflavone and the role of increased miR-16-5p expression on amentoflavone-induced inhibition (10)(11)(12)(13)(14)(15). However, the function of miR-16-5p in the progression of CRC remains unknown.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, the anticancer effect and the mechanism of action of amentoflavone in CRC are unknown. In this study, we demonstrated the anti-CRC cell migration, invasion, and EMT effect of amentoflavone and the role of increased miR-16-5p expression on amentoflavone-induced inhibition (10)(11)(12)(13)(14)(15). However, the function of miR-16-5p in the progression of CRC remains unknown.…”
Section: Discussionmentioning
confidence: 76%
“…MicroRNAs (miRNAs) are a large class of small noncoding RNAs (14). The miR-16 family comprises six mature miRNAs (miR15a/b, miR-16-5p, miR-195, miR-424, and miR-497) widely explored in various cancers and considered tumor suppressors that inhibit tumor progression (15)(16)(17)(18)(19)(20).…”
Section: Original Articlementioning
confidence: 99%
“…Alternatively, non-replicating species-specific RNA interference (RNAi) technologies disrupt physiological functions in a target organism to reduce reproductive output or cause death through ingestion or topical application to a target organism (e.g., Xu et al 2021). A critical component and benefit of the technology is that the RNAi compound can be developed and validated to be species-specific, ensuring other species are not harmed (e.g., only functional in Burmese pythons).…”
Section: Development Of New Control Toolsmentioning
confidence: 99%
“…It is obvious that viral mRNAs retain target sites for miRNAs ( Skalsky and Cullen, 2010 ), and that miRNAs can achieve the regulatory roles by targeting host mRNAs and/or viral mRNAs. The regulatory roles played by miRNAs include inhibiting or promoting viral replication and certain other pathobiology related effects ( Xu et al, 2021 ).…”
Section: General Interaction Modes Of Mirnas-infectious Virusesmentioning
confidence: 99%